Comparison of metabolic syndrome prevalence and characteristics using five different definitions in China: a population-based retrospective study - Ma, Keli; Liu, Haiyang; Guo, Leilei; Li, Jinlong; Lei, Yunxiao; Li, Xiaoping; Sun, Lu; Yang, Liu; Yuan, Ting; Wang, Congzhi; Zhang, Dongmei; Li, Jing; et al. (Frontiers in Public Health, 2024)
Background: Metabolic syndrome(MetS)is on the rise in developing countries and is characterized by a series of indications of metabolic disturbance. However, the prevalence of MetS varies under different definitions. The study aimed to compare five definitions of MetS in the China adult population, to explore their prevalence, characteristics and agreement.: The data for the retrospective study came from the China Health and Retirement Longitudinal Study(CHARLS), consisting of 9588 participants(≥45). MetS definitions from International Diabetes Federation(IDF)(2006), National Cholesterol Education Program Adult Treatment Panel Ⅲ(ATPⅢ)(2005),National Cholesterol Education Program Adult Treatment PanelⅢ(ATPⅢ)(2001), Chinese Diabetes society(CDS)(2004)and the World Health Organization(WHO)(1999).We used binary and multivariable logistic analysis to explore factors connected with MetS. Results: The five definitions of MetS led to different prevalence of MetS:34.52% by IDF(2006),38.63% by ATP (2005),25.94% by ATP(2001),26.31% by CDS(2004),21.57% by WHO(1999).According to the definition of IDF(2006)(22.32%vs45.06%), ATPⅢ(2005) definition (27.99%vs47.82%),ATPⅢ(2001) definition(15.37%vs35.07%),CDS( 2004) definition (19.96%vs31.80%), and WHO (1999) definition (17.44%vs25.14%), the prevalence of MetS in men was low but in women was high. The agreement between the five definitions for men was good except for the IDF ( 2006) definition and ATPⅢ ( 2001) definition (kappa =0.51), with kappa values from 0.64 to 0.85. For women, the agreement between the five definitions was good ranging from 0.67 to 0.95, however, except for the definition of CDS ( 2004) and the definition of IDF (2006) (kappa =0.44), the definition of WHO (1999) and the definition of IDF (2006) (kappa =0.55), and the definition of WHO (1999) and the definition of ATPⅢ (2005) (kappa =0.54). Binary logistic analysis indicated that although the impact and relevance varied by sex and definition, age, education, marital status, current residence, current smoking, alcohol using, taking activities and number of chronic diseases were factors connected to MetS.Conclusions: the prevalence and characteristics of the five definitions of MetS are different in the Chinese population. Therefore, it is vital to use the same definition for a country to diagnose MetS. On the other side, a lower prevalence in men than in women and the consistency of five MetS definitions are good in men but relatively poor in women.